Minor feelings : an Asian American reckoning - Hong, Cathy Park (One World, 2020)
"Asian Americans inhabit a purgatorial status: neither white enough nor black enough, unmentioned in most conversations about racial identity. In the popular imagination, Asian Americans are all high-achieving professionals. But in reality, this is the most economically divided group in the country, a tenuous alliance of people with roots from South Asia to East Asia to the Pacific Islands, from tech millionaires to service industry laborers. How do we speak honestly about the Asian American condition--if such a thing exists? Poet and essayist Cathy Park Hong fearlessly and provocatively confronts this thorny subject, blending memoir, cultural criticism, and history to expose the truth of racialized consciousness in America. Binding these essays together is Hong's theory of "minor feelings." As the daughter of Korean immigrants, Cathy Park Hong grew up steeped in shame, suspicion, and melancholy. She would later understand that these "minor feelings" occur when American optimism contradicts your own reality--when you believe the lies you're told about your own racial identity. With sly humor and a poet's searching mind, Hong uses her own story as a portal into a deeper examination of racial consciousness in America today. This intimate and devastating book traces her relationship to the English language, to shame and depression, to poetry and artmaking, and to family and female friendship. A radically honest work of art, Minor Feelings forms a portrait of one Asian American psyche--and of a writer's search to both uncover and speak the truth"--